El Niño: Malawi’s harvest of its staple food maize may fall by 22.5% this year - De Weerdt, Joachim; Arndt, Channing; Thurlow, James; Duchoslav, Jan; Glauber, Joseph W.; You, Liangzhi; Anderson, Weston (The Conversation, 2024)
Maize is the preferred staple of most of southern Africa. In Malawi it supplies two-thirds of national calorie intake. Nine out of 10 farming households produce maize and devote over 70% of their land to growing it. Most farming households are vulnerable to the rainfall patterns. Over 90% of farming households in the country rely solely on rain to irrigate their maize plants. We looked at possible weather pattern changes driven by El Niño – an unusual warming of surface waters in the eastern tropical Pacific Ocean – and their impact on maize production in Malawi. We did this by developing a model from historical district crop data and El Niño events since the 1980s. Econometric modelling, which uses statistics and mathematics, is useful in studying the cause and effect of relationships, in the case of weather patterns. Historically, two out of every three El Niño events have coincided with reduced maize harvests of, on average, 22.5%.